Multimodal mechanistic pathways in Alzheimer’s disease: toward an integrated model of pathogenesis - Cavan D. Souza; Shiva Murthy Nanjundappa; Nirupama Murali (International Journal of Basic & Clinical Pharmacology, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder marked by β-amyloid plaques, tau tangles, synaptic dysfunction, and large-scale network failure. While the amyloid cascade hypothesis has dominated, emerging evidence suggests distinct yet interacting amyloid and tau trajectories influenced by genetic, vascular, metabolic, and inflammatory factors. Understanding this multimodal convergence is key to redefining AD pathogenesis. Following PRISMA 2020 guidelines, mechanistic studies published from January 2016 to August 2025 were reviewed from pubmed and the cochrane library. Eligible studies provided original data on molecular, cellular, or systems-level mechanisms of AD. Findings were synthesized across seven domains: amyloid, tau, neuroinflammation, synaptic dysfunction, mitochondrial stress, metabolic dysregulation, and genetics. Across 22 studies, evidence supports a shift from a linear amyloid model to a multidimensional framework. Amyloid and tau initiate independently but later interact to accelerate degeneration. APOE ε4 carriers show amyloid-driven disease, while non-carriers exhibit tau-dominant progression, with females showing higher vulnerability. fMRI and DTI reveal early Default Mode Network and white matter disruption. Biomarkers (Aβ42, tau, NfL, neurogranin, SNAP25) detect early changes, while mitochondrial and glial dysfunction and vascular-metabolic stress further modulate progression. AD emerges from converging genetic, molecular, and network-level abnormalities. A multimodal approach integrating imaging, fluid biomarkers, and genetics offers promise for early detection, risk stratification, and personalized multi-target therapies.